A Review of Grazing Incidence Small‐ and Wide‐Angle X‐Ray Scattering Techniques for Exploring the Film Morphology of Organic Solar Cells. Issue 10 (6th August 2020) - Mahmood, Asif; Wang, Jin‐Liang
Abstract : In recent years, a rapid evolution of organic solar cells (OSCs) has been achieved by virtue of structural design of active layer materials and optimization of film morphology. Along with other characterization techniques, grazing incidence small‐ and wide‐angle X‐ray scattering (GISAXS and GIWAXS) have played significant role in deeper understanding of film morphology. Herein, the importance of these techniques is explained with examples from various aspects of OSCs. Different pre‐ and post‐processing conditions such as solvent effect, solvent additive, solvent, and thermal annealing are studied in the framework of these techniques. Moreover, the impact of donor:acceptor ratio and molecular weight of semiconductor on microstructure is also explored. Finally, the effect of chemical structure of organic semiconductors (both polymers and small molecules) on the film morphology is discussed. These techniques provide valuable information about crystallinity, phase separation, and domain size of nanostructured film morphology, which helps to optimize the film morphology and enhances the performance of OSCs. The role of these techniques will become more important as the mystery of film morphology still has to be solved. Abstract : Grazing incidence small‐ and wide‐angle X‐ray scattering (GISAXS and GIWAXS) are extensively used for the characterization of film morphology of organic solar cells (OSCs). Herein, the use of these techniques to find the effect of chemistry of active layer materials and different pre‐ and postprocessing conditions on the film morphology of OSCs is discussed.